Complicaciones de hernioplastia inguinal con técnica de Lichtenstein en pacientes que acuden al Hospital Manuel Ygnacio Monteros Valdivieso - Piedra Palomino, Carolina Estefanía (2023)
A hernia in the inguinal area is the result of an abnormal protrusion of tissue due to a defect in the surrounding wall. According to INEC, inguinal hernias represented 463 of the total hospital discharges in Loja in 2017. The following research work focuses on the management of this pathology, to its epidemiological factors, techniques related to recurrence and even hospital needs. Specifically, the main interested in knowing the frequency of inguinal hernias based on age and gender at Manuel Ygnacio Monteros Hospital in Loja, as well as identifying the anatomical location, and describing the complications that resulted from inguinal hernioplasty using the Lichtenstein technique. This is a quantitative, descriptive, cross-sectional study, with a total of 145 patients attending the Manuel Ygnacio Monteros Hospital, of which 75 patients underwent hernioplasty with the Lichtenstein technique. The data obtained from the patients' information registry, showed that 51% of the patients were male and over or equal to 60 years of age. Moreover, the 29% of patients showed pain on the left side. Additionally, forty-nine percent of the patients presented complications such as pain, recurrence of hernia and paresthesia. In conclusion, Lichtenstein hernioplasty presented fewer complications than expected, making it an appropriate technique for patients with this disease